MicroRNA as novel biomarkers and therapeutic targets in diabetic kidney disease: An update - Qinghua Cao; Xin‐Ming Chen; Chunling Huang; Carol A. Pollock (FASEB BioAdvances, 2019)
Abstract Diabetic kidney disease (DKD) is a life‐limiting condition characterized by progressive and irreversible loss of renal function. Currently, the estimated glomerular filtration rate (eGFR) and albuminuria are used as key markers to define DKD. However, they may not accurately indicate the degree of renal dysfunction and injury. Current therapeutic approaches for DKD, including attainment of blood pressure goals, optimal control of blood glucose and lipid levels, and the use of agents to block the renin‐angiotensin‐aldosterone system (RAAS) can only slow the progression of DKD. Hence, early diagnosis and innovative strategies are needed to both prevent and treat DKD. In recent years, a novel class of noncoding RNA, microRNAs (miRNAs) are reported to be involved in all biological processes, including cellular proliferation, apoptosis, and differentiation. miRNAs are small noncoding RNAs that regulate gene expression by posttranscriptional and epigenetic mechanisms. They are found to be in virtually all body fluids and used successfully as biomarkers for various diseases. Urinary miRNAs correlate with clinical and histologic parameters in DKD and differential urinary miRNA expression patterns have been reported. Kidney fibrosis is the common end stage of various CKD including DKD. Transforming growth factor‐β(TGF‐β) is regarded as the master regulator of kidney fibrosis, which is likely at least in part through regulating miRNA expression. miRNA are widely involved in the progression of DKD via many molecular mechanisms. In this review, the involvement of miRNA in fibrosis, inflammation, hypertrophy, autophagy, endoplasmic reticulum (ER) stress, oxidative stress, insulin resistance, and podocyte injury will be discussed, as these mechanisms are believed to offer new therapeutic targets that can be exploited to develop important treatments for DKD over the next decade.